The Impact of Homocysteine on the Risk of Hormone-Related Cancers: A Mendelian Randomization Study - He, Qian; Yang, Ze; Sun, Yandi; Qu, Zihao; Jia, Xueyao; Li, Jingjia; Lin, Yindan; Luo, Yan (Frontiers in Nutrition, 2021)
Abstract Background: Aberrant homocysteine level is associated with metabolic disorders and DNA damage, which may be involved in carcinogenesis of hormone-related cancers, but clinical results of observational studies are controversial. Here we investigated the causal relationships between plasma homocysteine and breast cancer (BRCA), prostate cancer (PrCa) and renal cell carcinoma (RCC) using Mendelian randomization (MR) analyses. Design and methods: To investigate the putative causal associations between homocysteine and aforementioned three types of cancers, a two-sample Mendelian randomization study was employed for the study. The primary strategy for summary data analyses was the inverse-variance weighted (IVW) approach. In our study, the SNPs excluded confounding factors through Linkage Disequilibrium (LD) and Phenoscanner tests were the instrumental variants(IVs), homocysteine is the exposure, and BRCA, PrCa and RCC are the outcomes. Single-nucleotide polymorphisms (SNPs) associated with homocysteine were extracted from a large genome-wide association studies (GWAS) meta-analysis of European participants (n=44,147). Summary Statistics of breast cancer were obtained from the latest and largest GWAS meta-analysis comprising of 82 studies from Breast Cancer Association Consortium (BCAC) studies, including women of European ancestry (133,384 cases and 113,789 controls); we obtained summary-level data from the GWAS meta-analysis of prostate cancer comprising 79,148 cases and 61,106 controls of European ancestry, and the dataset of RCC was a sex-specific GWAS meta-analysis comprising of two kidney cancer genome-wide scans for men（3227 cases and 4916 controls）and women (1992 cases and 3095 controls) of European ancestry. The MR-Egger and weight median analyses were applied for pleiotropy test. Results: The results showed null associations between plasma homocysteine levels and overall breast cancer (effect=0.97, 95% CI : 0.90-1.06, P=0.543), overall prostate cancer (effect=1.01, 95% CI : 0.93-1.11, P=0.774), RCC in men (effect=0.99, 95% CI : 0.73-1.34, P=0.929) and RCC in women (effect=0.89, 95% CI : 0.61-1.31, P=0.563). Conclusions: We found no putative causal associations between homocysteine and risk of BRCA, PrCa and RCC.